INVESTIGATING THE ROLE OF ENTREPRENEURIAL LITERACY AND DIGITAL ECONOMY LITERACY ON THE SUCCESS OF MSMES IN THE CULINARY SECTOR: WHY DOES ENTREPRENEURIAL MOTIVATION MATTER? - Ahmad, Muh. Ihsan Said; Rahmi; Rijal, Syamsu; Supatminingsih, Tuti; Hasan, Muhammad (UNIVERSITAS NEGERI SURABAYA, 2024)
The aim of this research is to gain knowledge and understanding regarding the influence of Entrepreneurial Literacy and Digital Economic Literacy on the Success of MSMEs in the Culinary Sector in Makassar City with Entrepreneurial Motivation as a Moderator Variable. The method used is quantitative research techniques with descriptive research type. The sample in the research was 100 Culinary MSME Business Actors. Data analysis uses the Partial Least Square Structural Equation Model (PLS- SEM). The research results obtained are, 1. Entrepreneurial literacy and digital economic literacy have an influence on entrepreneurial motivation; 2. Entrepreneurial literacy and digital economic literacy have a significant effect on business success; 3. Entrepreneurial motivation has a significant influence on business success; 4. Entrepreneurial motivation is able to mediate the relationship between entrepreneurial literacy and business success; 5. Entrepreneurial motivation is able to mediate the relationship between entrepreneurial literacy and business success.